Financial management and accountability issues in museums (a case study) - Ahmad, Halimah @ Nasibah; Saad, Natrah; Md Saleh, Md Suhaimi; Ismail, Mohamad Sharofi; Hassan, Nor Laili (INSInet Publications, 2016)
This case focuses on the problems faced by Lang Buana Museums in its effort to enhance the performance of the Museums and to discharge public accountability.Lang Buana Museums comprise the State Museum, the Alamaya Museum, the State Art Gallery, the State Royal Museum and the Raja Putra Memorial.The data collection process involved face-to-face interviews with the management and staff of the Lang Buana Museums in 2013. Furthermore, financial reports and other documentation were also analyzed.The analysis of this case study highlights a few inherent problems faced by the Museums.Specifically, the problems relate to lack of financial resources to fund capital expenditure, lack of staff, communication problem between the top management and the subordinates, resistance to change among staff, lack of innovativeness among the staff and lack of expertise in valuations of artefacts.It was further found that the problems faced by the museums relate to accountability issued relating to financial, management and program.Based on the findings of this case study, recommendations were provided and solutions were formulated to assist the management of these museums to solve identified problems and related accountability issues.